SiRNA carrying an (E)-vinylphosphonate moiety at the 5΄ end of the guide strand augments gene silencing by enhanced binding to human Argonaute-2. Issue 6 (28th November 2016) - Elkayam, Elad; Parmar, Rubina; Brown, Christopher R.; Willoughby, Jennifer L.; Theile, Christopher S.; Manoharan, Muthiah; Joshua-Tor, Leemor
Abstract: Efficient gene silencing by RNA interference (RNAi) in vivo requires the recognition and binding of the 5΄- phosphate of the guide strand of an siRNA by the Argonaute protein. However, for exogenous siRNAs it is limited by the rapid removal of the 5΄- phosphate of the guide strand by metabolic enzymes. Here, we have determined the crystal structure of human Argonaute-2 in complex with the metabolically stable 5΄-( E ) - vinylphosphonate (5΄- E -VP) guide RNA at 2.5-Å resolution. The structure demonstrates how the 5΄ binding site in the Mid domain of human Argonaute-2 is able to adjust the key residues in the 5΄-nucleotide binding pocket to compensate for the change introduced by the modified nucleotide. This observation also explains improved binding affinity of the 5΄- E -VP -modified siRNA to human Argonaute-2 in-vitro, as well as the enhanced silencing in the context of the trivalent N -acetylgalactosamine (GalNAc)-conjugated siRNA in mice relative to the un-modified siRNA.